2011
DOI: 10.1021/je200730m
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Vapor Pressures of Five Saturated Fatty Acid Ethyl Ester (FAEE) Components of Biodiesel

Abstract: Vapor pressures of five saturated fatty acid ethyl esters (FAEEs), ethyl hexanoate (or ethyl caproate), ethyl octanoate (or ethyl caprylate), ethyl decanoate (or ethyl caprate), ethyl dodecanoate (or ethyl laurate), and ethyl tetradecanoate (or ethyl myristate), were measured at pressures from 1 Pa to 180 kPa and temperatures from (253.15 to 463.15) K using a static apparatus. These esters are a light fraction present in biodiesel derived from palmist oil and copra oil (Ballerini and Alazard-Toux, Les biocarbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…(11) and (12) provided the values of the parameters (a, b, c and d) for Eqs. (11) and (12). The values of these parameters are mentioned in Table 8.…”
Section: Generalized Methods (Predictive Methods)mentioning
confidence: 99%
See 1 more Smart Citation
“…(11) and (12) provided the values of the parameters (a, b, c and d) for Eqs. (11) and (12). The values of these parameters are mentioned in Table 8.…”
Section: Generalized Methods (Predictive Methods)mentioning
confidence: 99%
“…The experimental vapor pressure data for FAME's as reported by Scott et al [8], Rose and Supina [9], Bonhorst et al [10] and for FAEE's as reported by Benziane et al [11] were used for this study. Total 244 data points for FAME's in the temperature range of 306-512 K and 55 data points for FAEE in the temperature range of 273-462 K were considered for the estimation of vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical properties like as vapour pressure [5,6], Flash point [7], densities and viscosities [8][9][10][11] and equilibrium data of biodiesel and its components, namely fatty acids methyl esters (FAME) or FAEE [12][13][14] have been determined with the objective to improve the biodiesel production and its use as energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Melting and transition temperatures of binary mixtures formed by ethyl caprate (2), ethyl laurate (3) and ethyl myristate (4) with ethyl linoleate(6). e…”
mentioning
confidence: 99%
“…This study is a continuation of research works on the thermodynamic properties of organic compounds present in diesel/biodiesel blends and phase equilibria of their mixtures [8,9]. It concerns the experimental determination and modeling of solid-liquid equilibria (LSE) of the binary system: Methyl palmitate (1) + Naphthalene (2).…”
Section: Introductionmentioning
confidence: 99%